1978
DOI: 10.1128/aem.36.2.213-216.1978
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone biotransformation by plant cell suspension cultures

Abstract: Progesterone was converted to 5alpha-pregnane-3alpha-ol-20-one, delta4-pregnene-20alpha-ol-3-one, delta4-pregnene-14alpha-ol-3,20-dione, delta4-pregnene-7beta,14alpha-diol-3,20-dione, and delta4-pregnene-6beta,11alpha-diol-3,20-dione by cell cultures of Lycopersicon esculentum. Cell cultures of Capsicum frutescens (green) metabolized progesterone to delta4-pregnene-20alpha-ol-3-one in very high yield, and Vinca rosea yielded delta4-pregnene-20beta-ol-3-one and delta4-pregnene-14alpha-ol-3,20-dione. A stereospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Janeczko and Skoczowski [28] reviewed the literature regarding sex hormones in plants and reported that androgens and progesterone are present in approximately 80% of the plant species studied, suggesting that industrial milling of other plant species could contribute to the environmental androgen load. Cultured plant cells in suspensions from Lycopersicon esculentum, Capsicum frutescens , and Vinca rosea have been shown to biotransform progesterone to a number of Δ 4 ‐pregnene hydroxylated androgens [29], although not as rapidly as certain bacteria do. Progesterone in plants may be involved in a natural defense response against parasites, as suggested for isoflavonoids that inhibit nematode infection in alfalfa [30].…”
Section: Discussionmentioning
confidence: 99%
“…Janeczko and Skoczowski [28] reviewed the literature regarding sex hormones in plants and reported that androgens and progesterone are present in approximately 80% of the plant species studied, suggesting that industrial milling of other plant species could contribute to the environmental androgen load. Cultured plant cells in suspensions from Lycopersicon esculentum, Capsicum frutescens , and Vinca rosea have been shown to biotransform progesterone to a number of Δ 4 ‐pregnene hydroxylated androgens [29], although not as rapidly as certain bacteria do. Progesterone in plants may be involved in a natural defense response against parasites, as suggested for isoflavonoids that inhibit nematode infection in alfalfa [30].…”
Section: Discussionmentioning
confidence: 99%